Efektivitas Penggunaan Peta Konsep Kitab Sharḥ Qaṭr al-Nadá wa-Ball al-Ṣadá pada pembelajaran Nahwu di Perguruan Tinggi Islam - Solekhudin, Achmad; Isnaini, Moch Amirul; Al Afghani, Rahardian (Alsina : Journal of Arabic Studies, 2023)
This study aims to evaluate the effectiveness of using the mind map from the Kitab Sharḥ Qaṭr al-Nadá wa-Ball al-Ṣadá in enhancing the learning of Qawāid Naḥwīyah among first-year students in the Arabic Language Education program at UIN Walisongo Semarang, class of 2023, consisting of 27 students. The research employed a quasi-experimental method with a one-group pre-test and post-test design. The researchers conducted data analysis using a t-test to assess the improvement in learning outcomes. The results showed that the average post-test score (75.11) increased significantly compared to the average pre-test score (44.44), with a p-value of 0.000, indicating a high significance level. These findings suggest that the intervention effectively improved the student's learning outcomes. Thus, the use of the concept map from the Kitab Sharḥ Qaṭr al-Nadá wa-Ball al-Ṣadá has proven to be an effective teaching strategy for Qawāid Naḥwīyah among students.